Direct observation of RuvAB-catalyzed branch migration of single Holliday junctions - Amit, Roee (National Academy of Sciences, 2004)
Holliday junctions form during DNA repair and homologous recombination processes. These processes entail branch migration, whereby the length of two arms of a cruciform increases at the expense of the two others. Branch migration is carried out in prokaryotic cells by the RuvAB motor complex. We study RuvAB-catalyzed branch migration by following the motion of a small paramagnetic bead tethered to a surface by two opposing arms of a single cruciform. The bead, pulled under the action of magnetic tweezers, exerts tension on the cruciform, which in turn transmits the force to a single RuvAB complex bound at the crossover point. This setup provides a unique means of measuring several kinetic parameters of interest such as the translocation rate, the processivity, and the force on the substrate against which the RuvAB complex cannot effect translocation. RuvAB-catalyzed branch migration proceeds with a small, discrete number of rates, supporting the view that the monomers comprising the RuvB hexameric rings are not functionally homogeneous and that dimers or trimers constitute the active subunits. The most frequently encountered rate, 98 ± 3 bp/sec, is approximately five times faster than previously estimated. The apparent processivity of branch migration between pauses of inactivity is ≈7,000 bp. Branch migration persists against opposing forces up to 23 pN.